A novel nonsense variant in MED12 associated with malformations in a female fetus. Issue 12 (22nd December 2021) - Faergeman, Soren Lejsted; Becher, Naja; Andreasen, Lotte; Christiansen, Marianne; Frost, Lise; Vogel, Ida
Abstract: Pathogenic variants in the MED12  gene located on the X‐chromosome have primarily been reported in males with Lujan‐Fryns syndrome, Ohdo syndrome and the Opits‐Kaveggia syndrome. However, earlier reports of female patients and female mice suggest that MED12 deficiency causes severe malformations. We report a novel example of a MED12 de novo nonsense variant in a female fetus with severe malformations identified by trio‐exome sequencing. This finding further expands the clinical spectrum of MED12 ‐related disorders, which is vital for prenatal diagnosis and genetic counselling of couples. Abstract : Pathogenic variants in MED12 located on the X‐chromosome are linked to intellectual disability and dysmorphism in males. We report a novel MED12 de novo nonsense variant in a female fetus with malformations, further expanding the clinical spectrum.